Evaluation the Effect of Different Methods of Disinfection on Surface Roughness of Soft Denture Lining Materials - Lamia T Rejab; Ihssan F Al-Takai (University of Mosul, College of Dentistry, 2013)
Aims: Aim of the study to evaluate the effect of two different disinfection methods for two periods of time on surface roughness of soft denture lining materials (Vertex and Molloplast-B). Materials and methods : The effect of two disinfection methods ,first chemical disinfection method (which include artificial saliva with saturated salt and artificial saliva with vinegar solution), and second microwave method on the surface roughness of soft denture lining materials for two periods of times (14 and 30 days) was evaluated, One hundred samples were prepared. ANOVA and Duncan,s multiple range test were performed to determine the significant difference among the tested groups at p ≤ 0.05% .Results: The results showed that the lowest value of surface roughness (Ra)value after 14 and 30 days for Vertex soft denture lining material was achieved with the microwave group, while the lowest value of surface roughness (Ra)value after 14 and 30 days for Molloplast-B was achieved with the distilled water. The highest value of surface roughness (Ra) for Vertex soft denture lining material was achieved with vinegar after 14 and 30 days., while for Molloplast-B was achieved with vinegar group after 14 days and with salt group after 30 days. Conclusion : The results of T-test Table showed that there were no statistically significant differences in surface roughness(Ra) value between Vertex and Molloplast -B soft denture lining materials after 14 and 30 days except for microwave group after 14 days at P value ≤ 0.05. Distilled water disinfection has less effect on the property than other chemical disinfection and microwave regimen. The effect of disinfection increase significantly with increasing period of time .